Classroom chronicles: through the eyeglasses of teachers at varying experience levels - Jarodzka, Halszka; van Driel, Sharisse; Catrysse, Leen; Crasborn, Frank (Frontiers in Education, 2023)
Teachers face the intricate task of managing diverse classroom situations, directly affecting student learning outcomes. Many preservice and beginning teachers, however, find classroom management challenging. Effective classroom management hinges on the teacher's ability to notice and interpret visual cues that signal potential issues -a proficiency termed 'professional vision'. In this study, we used mobile eye-tracking glasses to assess the professional vision of 22 preservice, 17 beginning, and 19 experienced teachers as they instructed their classes. Our findings revealed no discernible differences in the efficiency of visual processing across varying teaching experience levels throughout the lesson. Interestingly, by the lesson's end, preservice teachers demonstrated a slight uptick in fixation counts compared to the onset. As for perceptual span, overall teaching experience did not significantly influence the dispersion of fixations, though experienced teachers exhibited a more expansive visual span at the lesson's commencement than its conclusion. In examining mental effort, teaching experience did not notably impact the average fixation durations. Yet, preservice teachers registered a subtle decrease in fixation durations as the lesson progressed to its end. In conclusion, this study showed that professional vision manifests differently across teaching experience levels. Given its nuanced influence on classroom management and student engagement shown in prior research, our study underscores its importance in pedagogical training.